2014
DOI: 10.1039/c4cc01337a
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the crucial role of a nucleophile in Ziegler–Natta type Ir catalyzed polyaminoborane formation

Abstract: formation through dehydropolymerization of ammonia-borane by Brookhart's iridium pincer catalyst has been under intense scrutiny but a sound molecular level understanding has remained elusive. Herein, using DFT the mechanism outlined by us for IrH2POCOP catalyzed formation underscores the importance of generation of nucleophiles, in particular that of the metal bound NH2BH2 moiety armed with a nitrogen lone pair for chain initiation and chain propagation steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 27 publications
(5 reference statements)
3
75
0
1
Order By: Relevance
“…A recent computational study explored the mechanism of The Catalytic Dehydrocoupling of Amine-Boranes and Phosphine-Boranesthe polymerisation of H 2 B¼NH 2 by 30 (although concomitant dehydrogenation of the amine-borane was not probed) and also implicated a chain growth mechanism, as suggested experimentally by Manners. The proposed mechanism for propagation involves end chain growth; the lone pair on the NH 2 end of the chain interacts with the Lewis acidic BH 2 group of the entering H 2 B¼NH 2 molecule [29]. This suggested mechanism contrasts with a coordination insertion mechanism, in which a transient aminoborane inserts into a growing polymer chain at the metal centre, similar to Ziegler-Natta olefin polymerisation.…”
Section: Late Transition Metalsmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent computational study explored the mechanism of The Catalytic Dehydrocoupling of Amine-Boranes and Phosphine-Boranesthe polymerisation of H 2 B¼NH 2 by 30 (although concomitant dehydrogenation of the amine-borane was not probed) and also implicated a chain growth mechanism, as suggested experimentally by Manners. The proposed mechanism for propagation involves end chain growth; the lone pair on the NH 2 end of the chain interacts with the Lewis acidic BH 2 group of the entering H 2 B¼NH 2 molecule [29]. This suggested mechanism contrasts with a coordination insertion mechanism, in which a transient aminoborane inserts into a growing polymer chain at the metal centre, similar to Ziegler-Natta olefin polymerisation.…”
Section: Late Transition Metalsmentioning
confidence: 97%
“…Although cyclohexene trapping is still regarded as a useful method for detecting free aminoboranes, more recent studies have suggested that the absence of hydroboration does not necessarily reflect an absence of free aminoborane. It has been suggested that, if borazine formation (from aminoborane trimerisation/dehydrogenation) or hydroboration of cyclohexene are not kinetically competitive with metal-based BN oligomerisation/ polymerisation processes, Cy 2 B¼NH 2 will not be observed even if H 2 B¼NH 2 is present [21,28,29]. [30].…”
Section: Aminoboranes: Observation and Trappingmentioning
confidence: 98%
“…Paul has suggested, using DFT calculations, a mechanism for dehydropolymerization catalyzed by IrH 2 (POCOP), which resembles a nucleophilic head‐to‐tail polymerization (Scheme C) . Separate metal centers (i.e., “bicatalyst”) are responsible for the dehydrogenation and polymerization activity.…”
Section: Mechanismmentioning
confidence: 99%
“…There are caveats associated with this approach though, as the trapping is dependent on the relative rates of hydroboration versus polymerization, where nucleophilic assistance of the solvent can be key . Interestingly Paul has calculated B−N head‐to‐tail bond forming polymerization using the IrH 2 (POCOP) catalyst to be lower in energy than cyclohexene hydroboration; suggesting that even if free aminoborane is formed in this specific system, polymerization could well be favored over hydroboration in the experimental system.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation